The Unconstitutionality of article 10, I and § 5 of the Family Planning Law (Research, Society and Development, 2020)
The purpose of this article is to study Law n°. 9,263/96, which regulates the constitutional right to family planning, focusing on the provisions that establish requirements for voluntary sterilization, foreseen in art. 10, I and §5th. Based on the assumption that the current rules governing voluntary sterilization in Brazil are unjustifiably restrictive, the objective is to confront the law under examination with constitutional norms-principles. The present work was based on qualitative research and literature review, and with the application of deductive method, the results of the work showed that there is incompatibility between the infraconstitutional provisions examined and the Constitution, having the fragments under analysis unconstitutional.